The Influence of Socio-Economic Conditions on the Education of Children of Fishermen's Families at SDN 1 Dewakang Lompo, Pangkep Regency - Hasniah, Hasniah; Rahmawati, Rahmawati; Hartini, Hartini; Elpisah, Elpisah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to 1) find out the general description of the socio-economic conditions and education of children of fishermen's families at SDN 1 Dewakang Lompo, and 2) analyze the influence of socio-economic conditions on the education of children of fishermen's families at SDN 1 Dewakang Lompo. This type of research is quantitative research. The population in this study were all students at SDN 1 Dewakang Lompo as many as 205 people, The sampling technique used in this study was cluster random sampling and those selected were classes IV, V and VI as many as 80 people. The data collection technique used questionnaires and documentation. Based on the results obtained, the socio-economic conditions of students, as measured by the level of parental education, parental income, and type of work, have a significant effect on the education of children of fishermen at SDN 1 Dewakang Lompo. Support from parents, although limited by economic conditions and work, remains an important factor in the success of children's education. However, financial constraints and minimal learning facilities are the main challenges that students must face in achieving optimal academic achievement.